2012
DOI: 10.1111/j.1750-3841.2012.02860.x
|View full text |Cite
|
Sign up to set email alerts
|

Astringency of Foods May Not be Directly Related to Salivary Lubricity

Abstract: If astringency's mechanism can be elucidated, food producers will gain knowledge that will enable them to manufacture, alter, or treat the food in a way to retain its healthful attributes while minimizing the astringency. This knowledge will also benefit sensory scientists interested in the intensity perceptions of the sensations and will allow them to devise improved methods for the assessment of the attribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Present results suggest individual differences in salivary protein levels may be relevant for beverage systems containing polyphenols, consistent with [18], but that these differences may be less relevant in solid foods, especially those that are high in fat, as fat presumably provides lubricity. Moreover, the perception of substantial amounts of astringency in tannin spiked chocolate compound despite the high amount of fat in the oral cavity is consistent with the emerging consensus that astringency is not merely a tactile sensation that arises solely from delubrication [8, 43, 44]. …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Present results suggest individual differences in salivary protein levels may be relevant for beverage systems containing polyphenols, consistent with [18], but that these differences may be less relevant in solid foods, especially those that are high in fat, as fat presumably provides lubricity. Moreover, the perception of substantial amounts of astringency in tannin spiked chocolate compound despite the high amount of fat in the oral cavity is consistent with the emerging consensus that astringency is not merely a tactile sensation that arises solely from delubrication [8, 43, 44]. …”
Section: Discussionsupporting
confidence: 76%
“…Although the tactile nature of astringency is widely supported in the literature, to date, the mechanisms responsible for oral astringency have not been fully elucidated. Emerging evidence suggests astringency may arise via more than one mechanism [8, 43, 44]. Here, we confirm that SP D-value is significantly related to the perceived astringency and liking of astringents in solution, but even in these model systems, it only explains ~30% of the variance in perceived astringency, suggesting it does not capture the mechanistic basis of the percept in its entirety.…”
Section: Discussionsupporting
confidence: 48%
“…On the other hand, other authors [e.g. [36]], observed that these proteins are precipitated by alum and acid, but not by polyphenols, suggesting different involvement according to the type of astringent molecule.…”
Section: Mechanical Sensations (Astringency)mentioning
confidence: 78%
“…Astringency is described as "the complex of sensations due to shrinking, drawing or puckering of the epithelium as a result of exposure to substances such as alums or tannins" by the American Society for Testing of Materials [34]. Astringent molecules are mainly plant-based products, namely polyphenols, among which tannins [35], but also acids and metal alums [6] and other dehydrating agents such as alcohols [36], which can also create this subjective oral feeling.…”
Section: Mechanical Sensations (Astringency)mentioning
confidence: 99%
“…In addition, polyphenols are known to influence the physicochemical state of several common dietary components such as dairy proteins including caseins [3]. They are also implicated in the perception of astringency [4][5][6][7][8][9][10][11][12], a complex mouthfeel effect, which has marked effects on the perception of foods and beverages [13].…”
Section: Introductionmentioning
confidence: 99%